Cambio de patrones culturales y económicos generados por la migración Kukama Kukamiria en la zona Moronacocha, Iquitos 2024 - Peña Flores, Percy Gerber (2025)
The main objective of the investigation of the change in cultural and economic patterns generated by the Kukama kukamilla migration into the Morona Cocha Iquitos area was to describe the changes in cultural and economic patterns generated by the Kukama migration to the Morona Cocha area, Iquitos 2024. The The methodology used has been a qualitative approach, a descriptive type of research, with an ethnographic design, with a population of 9000 inhabitants including migrants, city dwellers and foreigners, and a sample of 50 families, one person represented each family, the technique of a semi-structured interview was used, with participant observation. Migrants do not maintain their identity as Kukama, Yutupis and others, and make limited or non-existent use of their first language and customs characteristic of their community. Furthermore, they do not express or share with other people the most significant elements of their culture in order to further reinforce it in the community. Furthermore, they tell us that they do not participate in social activities that represent the traditions of their community and, if they do get involved, it is usually when they meet visiting tourists.